The invisibility of Galician immigration and the production of a hybrid social identity in the new lands (São Paulo, 1880-1910) - Biccas, Maurilane de Souza; Vidal, Diana Gonçalves (Historia y Memoria de la Educación, 2020)
The article explores the characteristics of Galician emigration to Brazil between the late 19th and early 20th centuries, focusing on the São Paulo region. It is organized into two complementary parts. In the first one, it deals with the historiography on the subject, inquiring statistics and trying to examine the profile of the Galician migrant who seeks the ocean crossing. In the same section, it discusses what we consider the double invisibility of Galician immigration, mixed with the Portuguese from the northern Portugal or with the generality of Spanish immigration in the official records of entry into the country. In the second section, the Centro Español de Santos and the school created by it are the subject of analysis in order to understand how the Galician immigrants produced a hybrid social identity from an associative practice. In the Final Comments, some questions are asked about the denomination of the entity.